1978
DOI: 10.1152/ajpendo.1978.234.5.e480
|View full text |Cite
|
Sign up to set email alerts
|

Immunofluorescent localization of renin in mouse submaxillary gland and kidney.

Abstract: An antibody prepared against purified submaxillary renin was used to determine the site of renin concentration in male mice using immunofluorescent localization. The results provide direct evidence that the granular tubules of the submaxillary glands are the source of submaxillary renin. The antibody against submaxillary renin cross-reacts with kidney renin as evidenced by immunofluorescent localization in the juxtaglomerular apparatus of mouse kidney.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1979
1979
1985
1985

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Although EGF and renin have been localized immunocytochemically in GCT cells of the submandibular gland (Turkington et al, 1971;van Noorden et al, 1977;Gresik and Barka, 1977;Menzie et al, 1978;, immunoreactive proteases, including kallikreins, have been demonstrated in some cells of the striated ducts of all three major salivary glands under normal conditions (Ekfors and Hopsu-Havu, 1971;Orstavik et al, 1975;Simson et al, 1979;Gresik et al, 1981a). However, the subcellular components responsible for this subluminal staining have not yet been identified.…”
Section: Hormonally Treated Female Micementioning
confidence: 99%
“…Although EGF and renin have been localized immunocytochemically in GCT cells of the submandibular gland (Turkington et al, 1971;van Noorden et al, 1977;Gresik and Barka, 1977;Menzie et al, 1978;, immunoreactive proteases, including kallikreins, have been demonstrated in some cells of the striated ducts of all three major salivary glands under normal conditions (Ekfors and Hopsu-Havu, 1971;Orstavik et al, 1975;Simson et al, 1979;Gresik et al, 1981a). However, the subcellular components responsible for this subluminal staining have not yet been identified.…”
Section: Hormonally Treated Female Micementioning
confidence: 99%